Generation of induced pluripotent stem cell-derived mice by reprogramming of a mature NKT cell. (22nd May 2014) - Ren, Yue; Dashtsoodol, Nyambayar; Watarai, Hiroshi; Koseki, Haruhiko; Quan, Chengshi; Taniguchi, Masaru
Abstract : The successful generation of iPSC-derived mouse strains to study NKT cells Abstract: NKT cells are characterized by their expression of an NKT-cell-specific invariant antigen-receptor α chain encoded by Vα14Jα18 gene segments. These NKT cells bridge the innate and acquired immune systems to mediate effective and augmented responses; however, the limited number of NKT cells in vivo hampers their analysis. Here, two lines of induced pluripotent stem cell-derived mice (NKT-iPSC-derived mice) were generated by reprogramming of mature NKT cells, where one harbors both rearranged Vα14Jα18 and Vβ7 genes and the other carries rearranged Vα14Jα18 on both alleles but germline Vβ loci. The analysis of NKT-iPSC-derived mice showed a significant increase in NKT cell numbers with relatively normal frequencies of functional subsets, but significantly enhanced in some cases, and acquired functional NKT cell maturation in peripheral lymphoid organs. NKT-iPSC-derived mice also showed normal development of other immune cells except for the absence of γδT cells and disturbed development of conventional CD4 αβT cells. These results suggest that the NKT-iPSC-derived mice are a better model for NKT cell development and function study rather than transgenic mouse models reported previously and also that the presence of a pre-rearranged Vα14Jα18 in the natural chromosomal context favors the developmental fate of NKT cells.